Loco or no Loco? Holocene Climatic Fluctuations, Human Demography, and Community Based Management of Coastal Resources in Northern Chile - Santoro, Calogero M.; Gayo, Eugenia M.; Carter, Chris; Standen, Vivien G.; Castro, Victoria; Valenzuela, Daniela; De Pol-Holz, Ricardo; Marquet, Pablo A.; Latorre, Claudio (Frontiers in Earth Science, 2017)
The abundance of the southern Pacific mollusk loco (Concholepas concholepas), among other conspicuous marine supplies, are often cited as critical resources behind the long-term cultural and demographic fluctuations of prehistoric hunter-gatherers at the coastal Atacama Desert. These societies inhabited one of the world’s most productive marine environments flanked by one the world’s driest deserts. Both of these environments have witnessed significant ecological variation since people first colonized them at the end of the Pleistocene (c. 13,000 cal yr BP). Here, we examine the relationship between the relative abundance of shellfish (a staple resource) along a 9,500-year sequence of archaeological shell midden accumulations at Caleta (a small inlet or cove) Vitor, with past demographic trends (established via summed probability distributions of radiocarbon ages) and technological innovations together with paleoceanographic data on past primary productivity. We find that shellfish extraction varied considerably from one cultural period to the next in terms of the number of species and their abundance, with diversity increasing during periods of regionally decreased productivity. Such shifts in consumption patterns are considered community based management decisions, and for the most part they were synchronous with large and unusual regional demographic fluctuations experienced by prehistoric coastal societies in northern Chile. When taken together with their technological innovations, our data illustrates how these human groups tailored their socio-cultural patterns to what were often abrupt and prolonged environmental changes throughout the Holocene.